Perencanaan Investasi Pengelolaan Ayam Petelur - Ningsih, Febriyanti (Jurnal Teknik Industri, 2008)
The decision making at the time being will result several effects to the present condition. Therefore, before making a decision in investment, it is important to have an accurate analysis. This will minimize the possibility of failure. At the present condition, the management of CV. PELANGI FARM is having some problems in developing widening investment, that is in the laying pullet management sector because the company possesses adequate experience in this sector. The indicator used in the management of laying pullet farm is by using Nett Present Value (NPV) method, that is the acceptance of management counted from the 0 year and Payback Period Method (PPM) which is a parameter of investment payback. From the analysis, here researcher is able to suggest that with field of 4 ha the farm should have 18.000 poultry (chickens). The result of calculation using Net Present Value and payback Period Method whether by individual investment or loan in 5 years is: NPV with individual investment is Rp975,212,452; NPV with loan investment is Rp187,591,244.58; PPM with individual investment for 2 years, 2 months, 24 days; and PPM with loan investment for 4 years, 5 months, 20 days. From the result of analysis, it can be seen that in management of laying pullet farm with 18,000 chickens for 5 years whether by individual or loan investment, both of them are properly done.